Description of the Tadpole of Hylodes magalhaesi (Bokermann, 1964) (Anura: Hylodidae) - Gomes, Felipe Bittioli R. [UNESP]; Provete, Diogo B. [UNESP]; Martins, Itamar A. (Soc Study Amphibians Reptiles, 2012)
We describe the external morphology and internal oral features of tadpoles of the torrent frog Hylodes magalhaesi from its type locality in southeastern Brazil. The tadpole can be distinguished from others of the genus mainly by the size of marginal papillae gap, the number and distribution of marginal papillae rows, and the number of submarginal papillae. The internal oral features of H. magalhaesi are similar to Hylodes charadranaetes; however H. magalhaesi can be distinguished from other species by the number and shape of buccal floor arena papillae and by the number of the prepocket papillae.